Concise Review: Cell-Based Strategies in Bone Tissue Engineering and Regenerative Medicine. (3rd December 2013) - Ma, Jinling; Both, Sanne K.; Yang, Fang; Cui, Fu-Zhai; Pan, Juli; Meijer, Gert J.; Jansen, John A.; van den Beucken, Jeroen J.J.P.
Abstract : Cellular strategies play an important role in bone tissue engineering and regenerative medicine (BTE/RM). Variability in cell culture procedures (e.g., cell types, cell isolation and expansion, cell seeding methods, and preculture conditions before in vivo implantation) may influence experimental outcome. The present review provides an overview of the critical procedures during in vitro and in vivo phases for cell-based strategies (both monoculture and coculture) in BTE/RM. Abstract: : Cellular strategies play an important role in bone tissue engineering and regenerative medicine (BTE/RM). Variability in cell culture procedures (e.g., cell types, cell isolation and expansion, cell seeding methods, and preculture conditions before in vivo implantation) may influence experimental outcome. Meanwhile, outcomes from initial clinical trials are far behind those of animal studies, which is suggested to be related to insufficient nutrient and oxygen supply inside the BTE/RM constructs as some complex clinical implementations require bone regeneration in too large a quantity. Coculture strategies, in which angiogenic cells are introduced into osteogenic cell cultures, might provide a solution for improving vascularization and hence increasing bone formation for cell-based constructs. So far, preclinical studies have demonstrated that cell-based tissue-engineered constructs generally induce more bone formation compared with acellular constructs. Further, cocultures have been shown to enhance vascularization and bone formation compared with monocultures. However, translational efficacy from animal studies to clinical use requires improvement, and the role implanted cells play in clinical bone regeneration needs to be further elucidated. In view of this, the present review provides an overview of the critical procedures during in vitro and in vivo phases for cell-based strategies (both monoculture and coculture) in BTE/RM to achieve more standardized culture conditions for future studies, and hence enhance bone formation.